Numerical Assessment of Inter-Pillar Stability in Inclined Ore Bodies for Underground Mining Design - Mussin, A.; Imashev, A.; Yeskenova, G.; Matayev, A.; Suimbayeva, A.; Zhunusbekova, G.; Shaike, N. (Salehan Institute of Higher Education, 2025)
This paper presents a methodology for assessing the stability of stoping chambers and inter-chamber pillars (ICPs) during underground mining of ore bodies with varying dip angles. The objective is to determine optimal parameters for excavation elements (chamber width and pillar spacing) that ensure the stability of the mining system under fractured rock mass conditions. The Zhezkazgan deposit’s geomechanical properties were used as the modeling case study. The methodology includes geotechnical core mapping (with RQD, Q-system, and GSI classifications), laboratory strength testing, field–laboratory correlation, and numerical modeling using the finite element method. Particular focus is placed on the sensitivity of stability to variations in GSI, depth, and excavation geometry. The results indicate that increasing the dip angle significantly reduces the stability of both chambers and pillars. The novelty of this study lies in the comprehensive assessment of structural factors and excavation geometry on mass stability under site-specific geological conditions.